Training In Manufacturing Multipurpose Eco-Enzyme Liquids for Farmers Group - Djarot, Prasetyorini; Triastinurmiatiningsih; Haryani, Tri Saptari; Prihatini, Wahyu; Moerfiah; Ismanto; Rahayu, Sata Yoshida Srie; Sudrajat, Cecep (Jurnal Pengabdian Masyarakat Inovatif, 2024)
Eco-enzyme is an active ingredient from organic waste that can be used for various daily purposes such as fertilizer, herbicide, cleaning fluid, and even medicine, this is because it contains Lactobacillus, Asotobacter xylinum, yeast fungi, and lactic acid bacteria, enzymes (such as protease, amylase, lipase), minerals, and secondary metabolites (such as polyphenols, alkaloids, antioxidants). By utilizing ecoenzymes optimally, it will support the use of household organic waste with an environmentally friendly concept. And this is also an effort to reduce disruption to the environment due to landfills, which can be done by utilizing household organic waste to make eco-enzymes. The aim of this service is to provide training in making eco-enzymes as a multi-purpose liquid which will have an impact on waste utilization. Organic which is oriented towards maintaining a clean environment. The first method used was socialization and continued with presentation of material about what eco-enzymes, why we need to develop them, how to make eco-enzymes and how to use them. The material was delivered through a presentation using a projector and the production was carried out by demonstrating how to make eco-enzymes. This activity was carried out by delivering presentation material about eco-enzymes. The training was carried out at the homes of Tanah Baru Village residents with the permission of the Village Head. The training participants were farmers of the Tanah Baru Subdistrict Farmers Group, totalling 20 people and several village officials.  The training was held on June 13 2022 which included counselling and demonstrations on making eco-enzyme solutions from fruit peels and vegetable waste. The training participants seemed very enthusiastic by asking questions and having lots of discussions about eco-enzymes and their uses, participants also actively participated in manufacturing activities.